A polyester composition, its preparation method and application
By combining titanium dioxide, phosphorus-containing inorganic substances and sulfur-containing organic substances and controlling their ratios, the problem of low reflectivity retention of the existing polyester compositions is solved, and a polyester composition with excellent mechanical properties and high color retention is obtained, thereby achieving efficient silicone curing performance.
Patent Information
- Application Number
- CN202310332255.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-30
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-03-30
AI Technical Summary
Current polyester compositions for LED stents have low reflectivity retention and affect the curing of the packaging glue.
By combining titanium dioxide, phosphorus-containing inorganic substances and sulfur-containing organic substances, a polyester composition with excellent mechanical properties, high initial color and color retention after high temperature baking is obtained by regulating the ratio of titanium element content and component D.
The reflectivity retention rate is achieved to reach 98% to 99.2%, the tensile strength is reached 54 to 122MPa, and it has excellent silicone curing properties.
Smart Images

Figure CN116462941B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer compound compositions, and more specifically, to a polyester composition and a preparation method and application thereof. Background Art
[0002] The birth of light-emitting diodes (LEDs) has brought the lighting industry into the era of semiconductor lighting. LED light sources have the advantages of high reliability, high luminous power, low power consumption, fast response speed, long life, low price, and rich colors. As a chip carrier, LED brackets play both conductive and thermal roles and are an indispensable key component of LED devices. The existing materials used for LED brackets are mainly high-temperature resistant polyamide (PPA) and high-temperature resistant polyester (cyclohexyl dimethyl terephthalate, PCT). High-temperature resistant polyamide (mainly including PA46, PA6T, PA9T, etc.) has high initial whiteness, good heat resistance, high fluidity, is suitable for injection molding process and has low cost. It is currently the mainstream material for LED brackets, but the photothermal aging decay of high-temperature resistant polyamide materials is fast and can only be used for low-power products.
[0003] With the introduction of high-voltage LEDs, PCT has greater advantages in application in medium and high-power LED reflectors due to its excellent high-temperature resistance and discoloration performance. However, the greater the power, the more heat is generated during use. Long-term high-temperature environments require higher heat resistance of materials. Otherwise, the material will age and discolor too quickly, which will directly affect the brightness of the LED and reduce the service life of the lamp beads.
[0004] The prior art has improved the reflectivity, aging resistance and light stability of the PCT material itself, but the reflectivity retention is still low. For example, the prior art discloses a thermoplastic resin composition with light stability at high temperature, which ensures the reflectivity of the resin composition with the high whiteness of the sodium phosphate salt itself, and uses the sodium phosphate salt to effectively remove the acid that may be generated during the molding process of the thermoplastic resin composition. Although it is effective in improving the color retention, the retention effect is insufficient, and excessive addition of phosphorus elements will cause the packaging glue to be poisoned and unable to solidify. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects and shortcomings of the existing polyester composition for LED brackets, such as low reflectivity retention rate and influence on the curing of packaging glue, and provide a polyester composition, which combines titanium dioxide, phosphorus-containing inorganic substances and sulfur-containing organic substances, utilizes the color of titanium dioxide itself and its ultraviolet aging resistance, and is matched with phosphorus-containing inorganic substances and sulfur-containing organic substances, and regulates the ratio relationship between the titanium element content and component D, so as to obtain a polyester composition with excellent mechanical properties, high initial color, high color after high-temperature baking and high color retention rate.
[0006] Another object of the present invention is to provide a method for preparing the polyester composition.
[0007] Another object of the present invention is to provide application of the polyester composition in preparing an LED reflective plate.
[0008] Another object of the present invention is to provide an LED reflective bracket.
[0009] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0010] A polyester composition, comprising the following components in parts by weight:
[0011] A) 30 to 90 parts by weight of PCT resin;
[0012] B) 10 to 60 parts by weight of titanium dioxide;
[0013] C) 0 to 5 parts by weight of an auxiliary agent;
[0014] D) Phosphorus-containing inorganic substances and sulfur-containing organic substances;
[0015] The mass ratio of titanium element in component B to component D is (5.8-70):1; the mass ratio of phosphorus element to sulfur element in component D is (20-140).
[0016] The present invention uses titanium dioxide, phosphorus-containing inorganic substances and sulfur-containing organic substances in combination, utilizes the color of titanium dioxide itself and its resistance to ultraviolet aging, combines with the anti-yellowing effects of the phosphorus-containing inorganic substances and the sulfur-containing organic substances, and controls the ratio of titanium content and component D to obtain a polyester composition with excellent mechanical properties, high initial color, high color after high-temperature baking and high color retention.
[0017] Titanium dioxide is the most common white additive in LED because of its very white color and excellent resistance to ultraviolet aging. However, titanium dioxide, as a mineral addition, has a great damage to the mechanical properties of the material matrix. When the amount of titanium dioxide added is too much, it will seriously affect the mechanical properties of the material, and when the amount of titanium dioxide added is too little, the whiteness of the substrate will be reduced, resulting in insufficient reflectivity, which in turn leads to insufficient lumens of the lamp beads, affecting the brightness of the lamp beads. Moreover, during the use of the lamp beads, light and heat will be generated, making the plastic prone to aging and degradation, causing its color to turn yellow and dark, affecting the service life of the lamp beads. The inventors found that phosphorus-containing inorganic substances and sulfur-containing organic substances can be used as anti-yellowing additives to improve the yellowing resistance of plastics, thereby improving the reflectivity retention rate of LED materials; by regulating the titanium content and the ratio of component D (phosphorus-containing inorganic substances and sulfur-containing organic substances), the ultraviolet aging resistance of titanium dioxide can be combined with the yellowing resistance of phosphorus-containing inorganic substances and sulfur-containing organic substances, thereby obtaining a polyester composition with excellent mechanical properties, high initial color, color after high-temperature baking, and color retention. In addition, by adjusting the ratio of phosphorus-containing inorganic substances and sulfur-containing organic substances, it is possible to ensure good yellowing resistance without affecting the curing performance of the encapsulation glue. The study found that sulfur-containing organic substances have a greater impact on the yellowing of plastics and also affect the curing of the encapsulation glue. If too little is added, the yellowing resistance of the plastic will be poor, while too much will affect the curing of the encapsulation glue. Once the encapsulation glue cannot be cured, the subsequent process of making lamp beads will not be able to proceed normally. Phosphorus-containing inorganic substances have less effect on the curing of the encapsulation glue and also have certain yellowing resistance. When combined with sulfur-containing organic substances in a specific ratio, good yellowing resistance can be achieved without affecting the curing of the encapsulation glue.
[0018] The auxiliary agent may be one or more of an antioxidant, a light stabilizer, an impact modifier, a flame retardant, a fluorescent brightener, a lubricant, a plasticizer, a thickener, an antistatic agent, a release agent, and a pigment.
[0019] Specifically, the mass ratio of titanium element in component B to component D is (6.2-66.6):1; the mass ratio of phosphorus element to sulfur element in component D is (23.8-131.2).
[0020] The mass ratios of titanium, sulfur and phosphorus were measured using the ICP-AES method according to US EPA method 3052:1996.
[0021] Preferably, the mass ratio of the titanium element in the component B to the component D is (30-35):1.
[0022] Preferably, the mass ratio of phosphorus element to sulfur element in the component D is (40-60):1.
[0023] Preferably, the intrinsic viscosity of the PCT resin is 0.6-0.8 dL / g.
[0024] The intrinsic viscosity test method of PCT resin is as follows: 0.1250 g of PCT polyester is dissolved in 25 mL of a mixture solution of phenol and 1,1,2,2-tetrachloroethane (the mass ratio of phenol to 1,1,2,2-tetrachloroethane is 1:1), and the viscosity is measured using an Ubbelohde viscometer in a constant temperature water bath at 25±0.1°C.
[0025] Specifically, the phosphorus-containing inorganic substance is one or more of disodium dihydrogen pyrophosphate, sodium hydrogen phosphate, sodium pyrophosphate, sodium tripolyphosphate, sodium tetrapolyphosphate, sodium pentapolyphosphate and sodium hexametaphosphate; preferably, disodium dihydrogen pyrophosphate.
[0026] Specifically, the sulfur-containing organic matter is one or more of dilauryl thiodipropionate, distearyl thiodipropionate, didodecanol thiodipropionate, 2-naphthol, 5,5'-thiodisalicylic acid, 3,5-bis(tert-butylthio)benzyl acetate, bis(carboxymethyl)trithiocarbonate and bis(thiobenzoyl)disulfide; preferably distearyl thiodipropionate.
[0027] Preferably, the polyester composition further comprises 10 to 60 parts by weight of a reinforcing material.
[0028] Specifically, the reinforcing material is one or more of glass fiber, wollastonite, potassium titanate whisker, kaolin, talc and mica.
[0029] The present invention also protects a method for preparing the above polyester composition, comprising the following steps:
[0030] PCT resin, titanium dioxide, phosphorus-containing inorganic matter, sulfur-containing organic matter, reinforcing materials and additives are added into a twin-screw extruder, mixed evenly, and then melt-extruded and granulated to obtain a polyester composition.
[0031] In a specific embodiment, PCT resin, titanium dioxide, phosphorus-containing inorganic matter, sulfur-containing organic matter, and additives can be added to a twin-screw extruder from a main feed port, and reinforcing materials can be added to the twin-screw extruder from a side feed port. After uniform mixing, the mixture is melt-extruded and granulated to obtain a polyester composition.
[0032] Specifically, the temperature settings of the screw zones 1 to 9 of the twin-screw extruder are as follows: the temperature of zone 1 is 230-250°C, the temperature of zone 2 is 280-300°C, the temperature of zone 3 is 280-310°C, the temperature of zone 4 is 280-300°C, the temperature of zone 5 is 270-290°C, the temperature of zone 6 is 270-290°C, the temperature of zone 7 is 270-290°C, the temperature of zone 8 is 270-2900°C, the temperature of zone 9 is 270-290°C, and the main engine speed is 80r / min.
[0033] The use of the above polyester composition in the preparation of LED reflective plates is also within the protection scope of the present invention.
[0034] The present invention also protects an LED reflective bracket made from the polyester composition.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The invention provides a polyester composition, which combines titanium dioxide, phosphorus-containing inorganic substances and sulfur-containing organic substances, utilizes the color of titanium dioxide itself and its UV aging resistance, and is matched with phosphorus-containing inorganic substances and sulfur-containing organic substances, and adjusts the ratio of titanium content and phosphorus-containing inorganic substances and sulfur-containing organic substances, so as to obtain a polyester composition with excellent mechanical properties, high initial color, high color after high-temperature baking and high color retention, a reflectivity retention rate of 98% to 99.2%, a tensile strength of 54 to 122 MPa, and excellent silicone curing performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is a schematic diagram of the silicone curing test specimen. DETAILED DESCRIPTION
[0038] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0039] 1. Raw materials and reagents
[0040] PCT resin, intrinsic viscosity 0.719 dL / g, brand PCT0302, manufacturer Eastman Chemical Products Company;
[0041] The phosphorus-containing inorganic substance 1 is disodium dihydrogen pyrophosphate, brand name DHPP, manufactured by Anhui Zhongxu Biotechnology Co., Ltd., and the mass percentage of phosphorus element is 28% according to actual test results;
[0042] The phosphorus-containing inorganic substance 2 is phosphate, brand H10, manufacturer BRUGGOLEN, and the mass percentage of phosphorus element is 19% according to actual test results;
[0043] The sulfur-containing organic compound 1 is dioctadecyl thiodipropionate, brand name JYANOX-DSTDP, manufactured by Beijing Jiyi Chemical Co., Ltd., and the mass percentage of sulfur element is 5% according to the actual test results;
[0044] The sulfur-containing organic compound 2 is dilauryl thiodipropionate, brand name JYANOX-412S, manufactured by Beijing Jiyi Chemical Co., Ltd., and the mass percentage of sulfur element is 6% according to actual test results;
[0045] Titanium dioxide was commercially available, and the same type was used in other parallel experiments;
[0046] The reinforcing material was glass fiber, which was commercially available, and the same type was used in other parallel experiments.
[0047] 2. The polyester compositions of the embodiments and comparative examples of the present invention are prepared by the following preparation method:
[0048] After weighing each component according to the formula and mixing them evenly, the components are added into a twin-screw extruder for melt blending and extrusion granulation to obtain a thin-walled, highly light-transmitting, flame-retardant nylon composite material;
[0049] Among them, the glass fiber is added from the side feeding port of the twin-screw extruder, and the melt extrusion conditions of the twin-screw extruder are: the temperature of zone 1 is 230-250°C, the temperature of zone 2 is 280-300°C, the temperature of zone 3 is 280-310°C, the temperature of zone 4 is 280-300°C, the temperature of zone 5 is 270-290°C, the temperature of zone 6 is 270-290°C, the temperature of zone 7 is 270-290°C, the temperature of zone 8 is 270-2900°C, the temperature of zone 9 is 270-290°C, and the main engine speed is 80r / min.
[0050] 3. Performance testing
[0051] (1) Reflectivity test
[0052] The polyester compositions in the embodiments and comparative examples were injection molded into samples with a size of 60 mm×60 mm×0.8 mm, and the reflectivity value R0 of the sample at an initial wavelength of 460 nm was measured. The sample was then kept at a temperature of 180° C. for 4 hours, and the reflectivity value R1 at 460 nm was measured again. The reflectivity retention rate of the sample was calculated by Formula I.
[0053] R=R1 / R0*100%(Formula I)
[0054] (2) Silicone curing test
[0055] The polyester compositions in the examples and comparative examples were injection molded into Figure 1 For the sample shown, silica gel A and B (the grades of A and B are BQ-4242, purchased from Beiteli New Materials Co., Ltd.) were mixed evenly at a mass ratio of 1:4, and 0.2 g was dropped into the pit on the upper surface of the sample, so that the silica gel layer was spread flat on the bottom of the pit, and then the sample was placed in an oven, pre-cured at 80°C for 1 hour, and then heated to 150°C for further curing for 4 hours before the end. Take out the plate and directly observe the curing of the silica gel in the pit with the naked eye. Completely cured is represented by "⊙", and uncured is represented by "×".
[0056] (3) Element content test
[0057] According to US EPA method 3052:1996, the ICP-AES method is used for measurement. The sample is first configured to a sample with a concentration of C0, and then the concentration of titanium, sulfur and phosphorus in the sample can be obtained through testing. Ti , C P and C S , thus obtaining the mass ratio of each element. Because these elements have a small content, but have a key impact on the yellowing resistance and mechanical properties of the finished product, by directly measuring the element content in the sample, the exact value of the content of each element in the sample can be accurately known; in the sample preparation, it is inevitable to encounter fluctuations in the feeding process, and at this time, it is impossible to obtain the accurate content only through theoretical calculation.
[0058] Ti / D=C Ti / C 0* 100%;
[0059] P / S=C p / C S* 100%.
[0060] Examples 1 to 9
[0061] The weight proportions of the various components of the polyester compositions in Examples 1 to 9 are shown in Table 1.
[0062] Table 1 Polyester compositions in Examples 1 to 9
[0063]
[0064] Comparative Examples 1 to 7
[0065] The weight proportions of the various components in the polyester compositions of Comparative Examples 1 to 7 are shown in Table 2.
[0066] Table 2 Polyester compositions in Comparative Examples 1 to 7
[0067]
[0068]
[0069] The performance test results of the polyester compositions in the embodiments and comparative examples according to the above-mentioned methods are shown in Table 3.
[0070] Table 3 Test results of various embodiments and comparative examples
[0071] serial number Tensile strength / MPa Reflectivity retention rate / % Silicone curing properties Example 1 73 98.9 ⊙ Example 2 74 98.7 ⊙ Example 3 74 98.5 ⊙ Example 4 65 98.1 ⊙ Example 5 84 97.6 ⊙ Example 6 72 98.2 ⊙ Example 7 75 98.3 ⊙ Example 8 122 99.2 ⊙ Example 9 54 98 ⊙ Comparative Example 1 68 95.1 ⊙ Comparative Example 2 78 98.2 × Comparative Example 3 76 96.1 ⊙ Comparative Example 4 78 99.2 × Comparative Example 5 70 92.6 ⊙ Comparative Example 6 68 95.1 ⊙ Comparative Example 7 74 96.1 ⊙
[0072] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A polyester composition, characterized in that By weight, it includes the following components: A) 30-90 parts by weight of PCT resin; B) 10 to 60 parts by weight of titanium dioxide; C) 0 to 5 parts by weight of an auxiliary agent; D) phosphorus-containing inorganic substances and sulfur-containing organic substances; The mass ratio of titanium in component B to component D is (5.8-70):1; the mass ratio of phosphorus to sulfur in component D is (20-140):1; according to US EPA method 3052:1996, the ICP-AES method is used for measurement, the sample is first configured to a sample with a concentration of C0, and then the concentration of titanium, sulfur and phosphorus in the sample is obtained through testing. Ti , C P and C S , thereby obtaining the mass ratio of each element; The phosphorus-containing inorganic substance is one or more of disodium dihydrogen pyrophosphate, sodium hydrogen phosphate, sodium pyrophosphate, sodium tripolyphosphate, sodium tetrapolyphosphate, sodium pentapolyphosphate and sodium hexametaphosphate; The sulfur-containing organic matter is one or more of dilauryl thiodipropionate, distearyl thiodipropionate, didodecyl thiodipropionate, 2-naphthol, 5,5'-thiodisalicylic acid, 3,5-bis(tert-butylthio)benzyl acetate, bis(carboxymethyl)trithiocarbonate and bis(thiobenzoyl)disulfide; The polyester composition further comprises 10 to 60 parts by weight of a reinforcing material, wherein the reinforcing material is glass fiber.
2. The polyester composition according to claim 1, characterized in that The mass ratio of titanium element in component B to component D is (30-35):
1.
3. The polyester composition according to claim 2, characterized in that The mass ratio of phosphorus element to sulfur element in the component D is (40-60):
1.
4. The polyester composition according to any one of claims 1 to 3, characterized in that: The auxiliary agent is one or more of an antioxidant, a light stabilizer, an impact modifier, a flame retardant, a fluorescent brightener, a lubricant, a plasticizer, a thickener, an antistatic agent, a release agent, and a pigment.
5. A method for preparing the polyester composition according to any one of claims 1 to 4, characterized in that: The following steps are involved: PCT resin, titanium dioxide, phosphorus-containing inorganic matter, sulfur-containing organic matter, reinforcing materials and additives are added into a twin-screw extruder, mixed evenly, and then melt-extruded and granulated to obtain a polyester composition.
6. Use of the polyester composition according to any one of claims 1 to 4 in preparing an LED reflector.
7. An LED reflector bracket, characterized in that: The LED reflective bracket is made from the polyester composition according to any one of claims 1 to 4.
Citation Information
Patent Citations
Polyester composition for reflecting plate
CN104650547A
Polyester molding composition and preparation method and application thereof
CN109749371A